Determining the Rational Motion Intensity of Train Traffic Flows on the Railway Corridors with Account for Balance of Expenses on Traction Resources and Cargo Owners - Butko, Tetiana; Muzykin, Mykhailo; Prokhorchenko, Andrii; Nesterenko, Halyna; Prokhorchenko, Halyna (Transport and telecommunication, 2019)
The article proposes a method for determining the rational motion intensity of specific train traffic flows on railway transport corridors with account for balance of expenses on traction resources and cargo owners. A mathematical model based on stochastic optimization is developed, which allows to optimize, in the conditions of risks, the interval between trailing trains on the railway lines taking into account the limited resources of the traction rolling stock, the capacity of the stations and freight fronts at the cargo destination point. Solving this mathematical model allows to find a balance between the expenses for movement of train traffic flows from different railway lines to their terminal reference station and the expenses of a consignee, subject to the limitations of the technological logistics chain in cargo transportation. For the solution of this mathematical model, a Real-coded Genetic Algorithm (RGA) was used.